Otimização da produção de etanol 2G a partir de hexoses e pentoses - Suarez, Carlos Alberto Galeano (2014)
The industrial production of fuel ethanol and sugar generates the main byproduct of sugarcane bagasse, which is burned in boilers for power generation. However, as a lignocellulosic material (consisting basically of three polymers: cellulose, hemicellulose and lignin), bagasse can be reused for the production of second generation bioethanol (2G), which is a renewable and environmentally friendly biofuel. For industrial 2G bioethanol production becomes economically feasible, the use of all fermentable fractions present in the bagasse is required: C6 fraction (cellulose) and C5 fraction (hemicellulose). These fractions are subjected to hydrolysis processes that generate as main sugars glucose and xylose respectively. It is important, therefore, that the microorganism employed for the production of ethanol 2G is able to utilize all the sugars generated during the hydrolysis process. In this work we chose the yeast Saccharomyces cerevisiae to be the main microorganism used in the industrial production of ethanol, although unfortunately, this yeast is unable to ferment xylose. However, while S. cerevisiae does not use xylose, can ferment xylulose obtained by isomerization of xylose by the enzyme glucose isomerase. The objective of this study was to develop and evaluate technological alternatives for the production of ethanol 2G from hexoses and pentoses using wild S. cerevisiae. In relation to the C6 fraction, in this work two important aspects have been addressed: i) study of the operation regime of a fed-batch reactor enzymatic hydrolysis of the C6 fraction of bagasse from sugarcane, yielding values of final glucose concentration of 200 g.L-1, higher than 45 g.L-1 achieved in batch reactor; ii) kinetic modeling of complex systems (enzymatic hydrolysis of lignocellulosic substrates), in which an interpolator was developed using fuzzy logic as an important tool to represent the processes of enzymatic hydrolysis of lignocellulosic materials for rugged and reliable manner. Now, in relation to the C5 fraction initially applied simple techniques of Evolutionary Engineering, leading to the selection of a different strain of S. cerevisiae, adapted to assimilate xylulose in minimal medium and characterized by reduced formation of xylitol, which demonstrated a selectivity of ~7 getanol.gxilitol -1, significantly higher than the selectivity achieved by the wild strain of ~2 getanol.gxilitol -1. The selected strain was studied in batch cultures conducted in bench scale reactor under different conditions of oxygen limitation. It was found that the production of ethanol is favored over the formation of xylitol, keeping the flow of consumed xylulose above 0,5 mmol.gMS -1.h-1 for flow of oxygen consumption of 0.1 mmol.gMS -1.h-1, reaching in this condition selectivities around 4 getanol.gxilitol -1. For zero flow of oxygen (anaerobic culture) or above 0,3 mmol.gMS -1.h-1, ethanol production is drastically reduced , regardless of the flow xylulose assimilated by the cells.